Financial Analysis of Fishing Boat Rental Business at Kenyamukan Hamlet, District of North Sangatta, Regency of East Kutai - Rosdianto, Rosdianto (Sumatra Journal of Disaster, Geography and Geography Education, 2017)
Research aimed to determine the actual condition of fishing boat rental business, determined the profit earned by the entrepreneur of fishing boat rentals, and determine financial feasibility based on the criteria of investment discounted, including NPV, IRR, NBCR and Payback Period on fishing boat rental business in Kenyamukan county, District of North Sangatta, East Kutai Regency. Sampling was conducted by survey method and 10 person’s respondents. Research results showed the actual condition of fishing boat rental business its has been exist for 5 years, assisted by one crew (crew) and the rental cost its varies for Sangatta IDR 1,000,000 per trip, Miang Island IDR 2,000,000 per trip, Bira-Birahan IDR 4,000,000 per trip, Sekrat IDR 1,500,000 per trip, Teluk Lombok Rp 1,000,000 per trip, Manubar IDR 3,500,000 per trip and Sandaran IDR 6,000,000 per trip. Profit was earned from these businesses an average IDR 4,008,902 per month per respondent and an average IDR 48,106,825 per year per respondent. By the finacial a Fishing boat rental business in Kenyamukan County its reasonably to expanded at the present and future, this is evidenced by the value of the investment criteria that NPV = IDR. 316 079 901, IRR = 100%, Net BCR = 4.17, Pp = 1 year.